Modulation of Circulating Macrophage Migration Inhibitory Factor in the Elderly. (8th July 2014) - Rammos, Christos; Hendgen-Cotta, Ulrike B.; Pohl, Julia; Totzeck, Matthias; Luedike, Peter; Schulze, Volker T.; Kelm, Malte; Rassaf, Tienush
Abstract : Aging increases the risk for cardiovascular morbidity and mortality. Chronic low-grade inflammation deteriorates vascular function, increases age-related vascular stiffness, and affects hemodynamics. The proinflammatory cytokine macrophage migration inhibitory factor (MIF) is a major mediator of atherosclerosis. Plasma MIF levels are associated with arterial stiffness, a hallmark of vascular aging. Preclinical studies show that blockade of MIF leads to atherosclerotic plaque regression. Nutritional approaches provide opportunities to counteract age-related inflammation. Following a chronic dietary supplementation with the micronutrient nitrate has been demonstrated to improve vascular stiffness. Whether dietary nitrate affects circulating MIF levels is not known. In a randomized placebo-controlled, double-blinded study, elderly subjects received a dietary nitrate supplementation for 4 weeks. Dietary nitrate led to a decrease in plasma MIF levels in the elderly and to an improvement in vascular functions. This was associated with a reduction in central systolic blood pressure. Our data show that supplementation with dietary nitrate is associated with a reduction of circulating MIF levels along with an improvement in vascular function. This supports the concept of dietary approaches to modulate age-related changes of vascular functions.